2019
DOI: 10.1007/s40843-019-9477-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled nanostructured photosensitizer with aggregation-induced emission for enhanced photodynamic anticancer therapy

Abstract: Three nanostructured photosensitizers with aggregation-induced emission (AIE) characteristics based on 2,3-bis(4ʹ-(diphenylamino)-[1,1ʹ-biphenyl]-4-yl) fumaronitrile (BDBF) were prepared for image-guided photodynamic therapy (PDT). BDBF was encapsulated with Pluronic F-127 (F127) to form usual spherical nanoparticles (F127@BDBF NPs) with a red fluorescence emission and 9.8% fluorescence quantum yield (FQY). Moreover, BDBF self-assembled into nanorods (BDBF NRs) in water. Compared with F127@BDBF NPs, BDBF NRs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…In pursuit of higher possibility and convenience for in vivo application, hydrophobic AIE PSs usually need to be encapsulated within nanocarriers to form well-dispersed NPs with good water solubility and biocompatibility. 48,49,51,[136][137][138][139][140][141][142][143][144][145][146][147][148][149][150] More importantly, enhanced fluorescence intensity, promoted ROS generation and EPR effect-mediated tumor accumulation can be readily realized simultaneously after nanofabrication. For example, a hydrophobic AIE PS named TBTC8 with emission over 800 nm was designed and subsequently loaded into DSPE-PEG 2000 formed NPs for the PDT of 4T1 tumor-bearing mice by Liu and coworkers.…”
Section: Hydrophobicmentioning
confidence: 99%
“…In pursuit of higher possibility and convenience for in vivo application, hydrophobic AIE PSs usually need to be encapsulated within nanocarriers to form well-dispersed NPs with good water solubility and biocompatibility. 48,49,51,[136][137][138][139][140][141][142][143][144][145][146][147][148][149][150] More importantly, enhanced fluorescence intensity, promoted ROS generation and EPR effect-mediated tumor accumulation can be readily realized simultaneously after nanofabrication. For example, a hydrophobic AIE PS named TBTC8 with emission over 800 nm was designed and subsequently loaded into DSPE-PEG 2000 formed NPs for the PDT of 4T1 tumor-bearing mice by Liu and coworkers.…”
Section: Hydrophobicmentioning
confidence: 99%
“…In the context of combination therapy, chemotherapeutic substances may accumulate more intensively in the neoplastic tissue due to a “therapeutic window” [ 21 ]. This method is selective and the issue of combining photosensitizers with nanostructures is increasingly discussed [ 239 , 240 ]. An alternative “therapeutic window” mechanism involves creating perfusion/oxygen enhancement in neoplastic tissue.…”
Section: Why Are Hyperthermia and Pdt Used In Treatment? Why Are They A Good Option For Combination Treatment?mentioning
confidence: 99%
“…23,24 Oppositely, AIE PSs exhibit enhanced fluorescence and efficient 1 O 2 generation upon aggregation, making them excellent candidates for image-guided PDT. 18,25,26 It has been reported that AIEgens with cationic charge and suitable hydrophobicity tend to target the mitochondria of eukaryotic cells. 24,25,27−30 For example, cationic AIE PSs have been reported to distinguish cancer and normal cells based on the difference in plasma and mitochondrial membrane potential, achieving selective light-up and killing of cancer cells by PDT.…”
Section: Introductionmentioning
confidence: 99%